E-commerce Application to Improve the Sales Process of the Melatec Company (LACCEI, 2024)
The research work presented was developed with the purpose of determining the influence of an e-commerce application in the sales process of the company Melatec in the year 2022. The study model was pre-experimental, constituted with a sample of 15 product categories. Subsequently, an observation sheet was used for data collection. The Excel and XLSTAT statistical software and the Wilcoxon test were used for data analysis. The parameters covering the sales process were the percentage of complaints, returns, cancelled sales and completed sales. The results revealed a 55% decrease in the percentage of complaints, a 29% decrease in the percentage of returns, a 17% decrease in the percentage of cancelled sales and finally a 48% increase in the number of completed sales, compared to traditional sales. With respect to the above, it can be concluded that the application of e-commerce has a positive influence on the sales process of Melatec.